Reevaluation of baseline Widal titres in children: a cross-sectional survey of 250 children (1-15 years) in and around Davangere, Karnataka, India - H., Ramesh; B. P., Nagesh; Karanam, Sandeep; Yellinedi, Sankeerth; P. S., Suresh Babu (International Journal of Contemporary Pediatrics, 2016)
Background: Typhoid fever is a serious health problem in developing countries including India. Isolation of S. typhi by culture is the gold standard for diagnosis, but the positive cases are very less, time consuming and expensive, so the best alternative is Widal test. Widal test can be used as a diagnostic tool if we know the baseline titres in a particular community. Objective: To re-evaluate the baseline Widal titres in apparently healthy children in and around Davangere, and to find the significance of 1:160 titres in Widal test. Methods: Cross sectional study was done on 250 children. Tube agglutination test was done on 112 healthy and 138 children with minor nontyphoidal illness. Titres were studied in relation to age, sex, nutritional status and healthy children to minor nontyphoidal illness. Results: Out of 112 healthy children, 52.7% had titres less than 1: 20, 25% had 1:20, 18.8% had 1:40 and 3.6% had a titre level of 1:80 for ‘O’ antigen of S. typhi. 63% children had a titre of less than 1: 20, 21.4% had 1:20, 8% for 1:40 and 7.1% had a titre of 1:80 for ‘H’ antigen of S. typhi. For ‘H’ antigen of S. paratyphi A the titres for less than 1:20 were 83%, 8% cases had a titre of 1:20 and 4.5% cases had titre levels of 1:40 and 1:80. No children had a titre value of ≥1:160 for both S. typhi and paratyphi A in the healthy children group. Conclusions: The baseline titres of healthy children in all the age groups and both sex is ≤ 1:80 for ‘O’ and ‘H’ antigen of S. typhi and ‘H’ antigen of S. paratyphi A.